Becoming a World-Class University: The case of King Abdulaziz University - Tayeb, Osama; Zahed, Adnan; Ritzen, Jozef (Springer Nature, 2016)
Higher Education; Administration, Organization and Leadership; Educational Policy and Politics; International and Comparative Education; Knowledge - Discourse; Universities; Research; Community